Modification method of ceramic particles, ceramic reinforced high chromium iron-based composite material and preparation method of ceramic reinforced high chromium iron-based composite material
By coarsizing, sensitizing, activating and chemical plating of ceramic particles, combined with ceramic powder coating, the problem of insufficient connection strength between ceramic particles and metal matrix is solved, and the hardness and wear resistance of composite materials are improved. It is suitable for harsh labor. Mechanical equipment.
Patent Information
- Application Number
- CN202411132518.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, the connection strength between ceramic particles and metal matrix is insufficient, resulting in chemical reactions and decomposition of ceramic materials at high temperatures, affecting the mechanical strength and wear resistance of the materials, and the existing surface modification methods consume energy and time. long.
Coarse, sensitization, activation and electroless plating are used to surface modify SiC or ZTA ceramic particles, and coat them with ceramic powder to form a metallized modification layer and protective layer to enhance the interface bond between the ceramic particles and the metal matrix. strength.
It realizes high connection strength between ceramic particles and metal matrix, reduces chemical reactions and decomposition, improves the hardness and wear resistance of composite materials, is suitable for wear-resistant parts of mechanical equipment in severe working conditions, and is simple in process and low in cost. .
Smart Images

Figure CN119243131A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a modification method of ceramic particles and a ceramic-reinforced high-chromium iron-based composite material and a preparation method thereof. Background Art
[0002] In order to adapt to the rapid development of modern industry, the operation speed of mechanical equipment is getting faster and faster, and the wear of mechanical parts is becoming more and more serious, resulting in huge material and energy losses. Especially in the fields of metallurgy, mining, coal, building materials and other harsh working conditions, the economic losses caused by material wear are very alarming. High chromium cast iron HCCI has strong toughness, but poor wear resistance; ceramic materials have high hardness but poor toughness, easy to break, and difficult to process. If ceramics and metals can be made into composite materials, the performance characteristics of the two materials can be brought into play. For example, CN112725649A discloses that the surface of ceramic particles is coated with a binder and then uniformly coated with Ti-Cu-Ni metal powder and dried, and then the Ti-Cu-Ni metal modified ceramic particles are mixed with metal matrix powder to form a composite material compact, and a vacuum sintering or casting method is used to prepare a ceramic particle reinforced metal matrix composite material or a surface local reinforced composite material. CN111187939B, CN117488130A, etc. use particles and iron-based materials to mix to make composite materials. Compared with powder, adding large particles to the iron-based material can better improve the mechanical properties of the composite materials. However, the wettability and chemical stability between the granular ceramic material and the metal matrix will affect the mechanical strength of the material.
[0003] Take SiC ceramic particles as an example. Although SiC ceramics have good performance, they will have a violent chemical reaction with molten iron at high temperature. In order to reduce the reaction, surface modification is required. Surface modification usually involves slightly oxidizing silicon carbide at high temperature to form a dense SiO2 oxide film on its surface. However, this surface modification method takes a long time and consumes a lot of energy. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for modifying ceramic particles and a ceramic-reinforced high-chromium iron-based composite material and a preparation method thereof. The modification method can quickly achieve surface modification of ceramic particles and prevent decomposition of ceramic particles, effectively increase the connection strength between ceramic particles and metal-based materials, thereby preparing a ceramic-reinforced high-chromium iron-based composite material with high hardness and high wear resistance, providing technical support for the development of wear-resistant parts for mechanical equipment in harsh working conditions such as metallurgy, mining, coal, and building materials.
[0006] (II) Technical solution
[0007] In a first aspect, the present invention provides a method for modifying ceramic particles, comprising the following steps:
[0008] S1. Decontamination: cleaning and decontaminating SiC particles and / or ZTA (zirconia toughened alumina) particles;
[0009] S2. Roughening: Use a roughening liquid to roughen the surface of the ceramic particles, the roughening liquid is a hydrofluoric acid solution with a mass concentration of 2-2.5%;
[0010] S3, sensitization: remove the roughening solution remaining on the surface of the ceramic particles, and transfer the ceramic particles into the sensitizing solution, which is an acidified solution containing 0.06-0.08 mol / L divalent tin;
[0011] S4, activation: transferring the ceramic particles into an activation solution, wherein the activation solution is an acidified solution containing 0.0012-0.0024 mol / L divalent palladium;
[0012] S5. Chemical plating: The ceramic particles are chemically plated using a chemical plating solution, wherein the chemical plating solution contains: 20-30 g / L NiSO4, 12-18 g / L C6H8O7, 8-12 mL / L C3H6O3, 8-12 mL / L (NH4)2MoO4, 25-35 g / L NaH2PO2 and 20-30 g / L CH3COONa; the pH of the chemical plating solution is 5.0-5.2;
[0013] S6. Coating: Ceramic particles are coated with ceramic powders. The coating method is as follows: water glass is used as an adhesive, ceramic powders and the adhesive are mixed in a mass ratio of 1:1.8-2.2 to form a coating material, and the ceramic particles are coated with the coating material.
[0014] According to a preferred embodiment of the present invention, in S1: the ceramic particles are placed in ethanol at room temperature and ultrasonically cleaned for 3-10 minutes.
[0015] According to a preferred embodiment of the present invention, in S1: the average particle size of the ceramic particles is 2 mm, and dust and impurities on the surface of the particles are washed away by washing.
[0016] According to a preferred embodiment of the present invention, in S2: first use deionized water to wash the ethanol remaining on the surface of the ceramic particles and then dry them, then transfer the ceramic particles into the roughening solution and soak them for 8-15 minutes, stirring or shaking the container continuously during the soaking process; the common concentration of hydrofluoric acid is 40-44%, which is diluted 20 times with deionized water to obtain a diluted hydrofluoric acid solution, i.e., the roughening solution. After the roughening treatment, the oxide layer on the surface of the ceramic particles is removed and small pits are formed on the surface of the ceramic particles, thereby increasing the specific surface area of the ceramic particles.
[0017] According to a preferred embodiment of the present invention, in S3: first use deionized water to wash the residue on the surface of the ceramic particles to obtain a roughening solution, and then transfer it to the sensitizing solution and soak it for 25-35 minutes, stirring or shaking the container continuously during the soaking process. When preparing the sensitizing solution, weigh an appropriate amount of SnCl2·2H2O solid, add it to deionized water, the solution is milky white, and then add an appropriate amount of hydrochloric acid to make the solution clear, and then add deionized water until the sensitizing solution reaches a predetermined concentration. Through the sensitization treatment, the divalent tin ions are attached to the tiny pits on the surface of the ceramic particles.
[0018] According to a preferred embodiment of the present invention, in S4: the ceramic particles are placed in the activation solution and soaked for 16-24 minutes, and the container is continuously stirred or shaken during the soaking process. The preparation method of the activation solution is: weigh PdCl2, add it to deionized water, and then add an appropriate amount of hydrochloric acid to completely dissolve PdCl2 and present a brownish yellow color. The container is continuously stirred or shaken during the soaking process to make Pd 2+ As much as possible is reduced to metallic Pd, and a large number of Pd catalytic nuclei are covered on the surface of the ceramic particles to prepare for chemical plating.
[0019] According to a preferred embodiment of the present invention, in S5: the chemical plating solution formula is: 25g / L NiSO4, 15g / L C6H8O7, 10mL / L C3H6O3, 10mL / L (NH4)2MoO4, 30g / L NaH2PO2 and 25g / L CH3COONa; the pH of the chemical plating solution is 5.0-5.2. Under the catalytic action of the Pd crystal nucleus, the Ni ions in the chemical plating solution can be quickly reduced to a metal nickel film by the reducing agent in the chemical plating solution, so that the metal nickel film covers the surface of the ceramic particles, completing the metallization modification of the ceramic particles.
[0020] According to a preferred embodiment of the present invention, in S5: during the chemical plating process, the chemical plating solution is heated in a water bath to maintain the chemical plating temperature at 75-82° C., and the chemical plating time is 40-90 min.
[0021] According to a preferred embodiment of the present invention, in S6: in the coating material, the ceramic powder is composed of a mixture of silicon dioxide, aluminum oxide, copper oxide, boron carbide and titanium dioxide; during the coating process, the coating material and the ceramic particles are mixed at a ratio of 6.5-7.5:100, and are placed in a mixer for stirring and mixing, so that the coating material is coated on the surface of the ceramic particles to protect the ceramic particles. The ceramic powder is also used as a casting infiltration agent, so that the subsequent high-chromium cast iron molten metal can penetrate into the interior of the ceramic preform, improve the interface bonding strength between the ceramic particles and the high-chromium cast iron metal matrix, and obtain a ceramic-reinforced high-chromium iron-based composite material with high hardness and high wear resistance. The composite material is very suitable for manufacturing wear-resistant parts or high-load parts of mechanical equipment in harsh working conditions such as metallurgy, mining, coal, and building materials. Preferably, the ceramic powder is composed of a mixture of silicon dioxide, aluminum oxide, copper oxide, boron carbide and titanium dioxide in a mass ratio of 1-3:1-3:1-3:1-3:1-3.
[0022] In a second aspect, the present invention provides a method for preparing a ceramic reinforced high-chromium iron-based composite material, comprising:
[0023] Step 1: pouring the ceramic particles modified by the above modification method into a mold and drying them to obtain a ceramic preform;
[0024] Step 2: Assemble the ceramic preform and the mold cavity, cast the smelted high-chromium cast iron metal liquid at the casting temperature, cool it, and demold it; the high-chromium cast iron metal liquid penetrates into the ceramic preform to form a composite body with the ceramic preform.
[0025] According to a preferred embodiment of the present invention, in step 1: when making the ceramic preform, iron nails are embedded in the bottom so as to be subsequently fixed in the mold cavity, and the ceramic preform is hardened naturally or dried.
[0026] Before the adhesive water glass in the coating material is completely dry, the stirred and mixed mixture of ceramic particles and coating auxiliary materials is poured into a mold, and naturally dried and formed or lightly pressed under gravity to obtain a ceramic preform, so that the melt can penetrate into the pores of the ceramic preform when the metal-based melt is cast.
[0027] According to a preferred embodiment of the present invention, in step 2: high chromium cast iron liquid is cast at 1580°C. At the casting temperature, the high chromium cast iron liquid penetrates into the pores of the ceramic preform to form a ceramic reinforced high chromium iron-based composite material, recorded as SiC (or ZTA) @Ni / HCCI.
[0028] In a third aspect, the present invention further provides a ceramic-reinforced high-chromium iron-based composite material, which is prepared by the preparation method of the above embodiment. The ceramic-reinforced high-chromium iron-based composite material can bear and transfer loads well, and has the advantages of low friction coefficient, high hardness, high wear resistance, etc.
[0029] (III) Beneficial effects
[0030] The technical effect of the present invention is that the present invention performs methods such as coarsening, sensitizing, activating and chemically plating on ceramic particles such as SiC and / or ZTA, which can achieve rapid metallization modification of the surface of ceramic particles, and then uses ceramic micropowder to coat the surface of ceramic particles, which can reduce the reaction between ceramic particles and metal melts and the oxidative decomposition of ceramic particles, and enhance the connection strength between ceramic particles and metal matrix, thereby ensuring the performance of the composite material. The use of the ceramic micropowder coating can, on the one hand, reduce the degree of interface reaction and improve the interface structure; on the other hand, the ceramic micropowder acts as a casting infiltrant, making it easier for the metal matrix melt to penetrate into the pores of the ceramic preform and the metal melt is integrated with the ceramic preform after solidification, thereby obtaining a ceramic-reinforced high-chromium iron-based composite material, which has a low friction coefficient, high hardness and high wear resistance, and is suitable for making vulnerable and consumable parts of mechanical equipment in harsh working conditions such as metallurgy, mining, coal, and building materials.
[0031] The present invention uses SiC and / or ZTA particles as reinforcements and compounds them with a high chromium iron matrix with good toughness, so that the composite material has higher hardness and better wear resistance; the casting is performed by the casting infiltration method, which is easy to prepare, can be mass-produced, has low cost and high efficiency. Chemical plating and ceramic micropowders jointly improve the interface between ceramic and metal matrix, can quickly modify the ceramic surface, reduce the decomposition of ceramic particles when casting the metal matrix melt, and enhance the connection strength between the two. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 SEM images of SiC ceramic particles (a) and ZTA ceramic particles (b).
[0033] Figure 2 This is a photo of the ceramic reinforced high chromium iron-based composite material of Example 1-2.
[0034] Figure 3 These are SEM images of cross sections of the ceramic-reinforced high-chromium iron-based composite products SiC@Ni / HCCI and ZTA@Ni / HCCI of Examples 1-2 and SEM images of cross sections of SiC / HCCI and ZTA / HCCI prepared in Comparative Examples 1-2.
[0035] Figure 4 The hardness of the ceramic-reinforced high-chromium iron-based composite products SiC@Ni / HCCI and ZTA@Ni / HCCI of Examples 1-2, the SiC / HCCI and ZTA / HCCI prepared in Comparative Examples 1-2, and the high-chromium iron HCCI without ceramic reinforcement is compared.
[0036] Figure 5The friction coefficients of the ceramic-reinforced high-chromium iron-based composite products SiC@Ni / HCCI and ZTA@Ni / HCCI of Examples 1-2, the SiC / HCCI and ZTA / HCCI prepared in Comparative Examples 1-2, and the high-chromium iron HCCI without ceramic reinforcement are compared. DETAILED DESCRIPTION
[0037] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0038] Example 1
[0039] This embodiment provides a ceramic reinforced high chromium iron-based composite material, and the preparation method thereof is as follows:
[0040] (1) Decontamination: Take an appropriate amount of SiC ceramic particles, soak them in anhydrous ethanol at room temperature, and clean them in an ultrasonic cleaner for 5 minutes. The SiC ceramic particles are 2 mm in size. The dust and impurities on the surface of the particles are washed away by cleaning. The SEM of SiC ceramic particles is as follows Figure 1 As shown in (a).
[0041] (2) Roughening: After decontamination, wash the ceramic particles three times with deionized water to remove as much residual anhydrous ethanol as possible and then dry them. Then soak the silicon carbide particles in the roughening solution for 10 minutes, and shake the reaction container continuously during soaking. The roughening solution is prepared from 10mL of hydrofluoric acid (mass concentration 40%) and an appropriate amount of deionized water to make 200mL of roughening solution. The ratio of hydrofluoric acid to deionized water is 1:19. Through roughening, the oxide layer on the surface of the ceramic particles can be removed and small pits can be formed on the surface of the ceramic particles.
[0042] (3) Sensitization: Wash the ceramic particles after the roughening step three times with deionized water to remove the residual hydrofluoric acid, then put the ceramic particles into the prepared sensitizing solution and soak for 30 minutes. The reaction container must be shaken continuously during soaking. The main component of the sensitizing solution is 15g / L SnCl2·2H2O. When preparing 200mL of sensitizing solution, weigh 3g of SnCl2·2H2O solid and add it to an appropriate amount of deionized water. The solution will appear milky white. Then add an appropriate amount of hydrochloric acid to make the stannous chloride solution clear, and then add deionized water until the sensitizing solution reaches 200mL. During the sensitization process, the reaction container needs to be shaken several times to allow more divalent tin ions to adhere to the tiny pits on the surface of the ceramic particles.
[0043] (4) Activation: Place the ceramic particles in the activation solution and soak for 20 minutes. The reaction container must be shaken continuously during the soaking process. The main component of the activation solution is 0.25g / L PdCl2. When preparing the activation solution, first weigh 0.05g of PdCl2 particles and add it to deionized water to dissolve it in deionized water. Take 2mL of hydrochloric acid and add it. The solution will turn brown and continue to stir until PdCl2 is completely dissolved. During the activation process, the reaction container must be shaken several times to make Pd 2+ As much as possible is reduced to metallic Pd, covering a large number of Pd catalytic nuclei on the surface of the ceramic particles.
[0044] (5) Chemical plating: A chemical plating layer is plated on the surface of the ceramic particles after decontamination, roughening, sensitization and activation by chemical plating. The chemical plating solution formula is 25g / L NiSO4, 15g / L C6H8O7, 10mL / LC3H6O3, 10mL / L(NH4)2MoO4, 30g / LNaH2PO2, 25g / L CH3COONa, and during the chemical plating process, the chemical plating solution is heated in a water bath to a temperature of 80°C, the pH is maintained between 5.0-5.2, and the plating time is 80 minutes. Under the catalytic action of the Pd crystal nucleus, the Ni ions in the chemical plating solution can be quickly reduced to a metal nickel film by the reducing agent in the chemical plating solution, so that the metal nickel film covers the surface of the ceramic particles, completing the metallization modification of the ceramic particles. The surface of the metallized ceramic particles is covered with a Ni alloy plating layer.
[0045] (6) Preparation of ceramic preform: Ceramic powder is used to coat the surface of ceramic particles to form a ceramic preform. Water glass is used as a binder and ceramic powder is used as a casting infiltrant. The binder and the casting infiltrant are dissolved in a ratio of 2:1 to prepare a coating material. The prepared coating material and ceramic particles are then put into a blender at a mass ratio of 7:100 and stirred evenly so that the coating material fully coats the ceramic particles. The ceramic powder is composed of silicon dioxide, aluminum oxide, copper oxide, boron carbide and titanium dioxide mixed in a ratio of 3:1:1:2:2.
[0046] The uniformly stirred ceramic particles and coating material are poured into a foam mold and dried to form a cylindrical preform. The cylindrical preform has a diameter of 20 mm and a height of 10 mm. After the preform is solidified, it is fixed in the mold cavity and waits for pouring. In the process of preparing the ceramic preform, an iron nail is inserted into the bottom of the preform so that it can be fixed in the mold cavity later, and the prepared ceramic preform is dried and hardened.
[0047] (7) Preparation of composite materials: The prepared ceramic preform is assembled with the foam pattern and the casting system, the shape is trimmed and the slurry is applied, and the preform is placed in a sand box for casting.
[0048] Before casting, the solidification process of the composite material was simulated using simulation software, and the appropriate temperature was found. The pouring temperature was set to 1480°C, 1530°C, 1580°C and 1630°C. By analyzing the thermal stress distribution of the metal, casting was finally carried out at 1580°C.
[0049] During the casting process, an electric arc furnace is used to melt high chromium iron. After the high chromium iron is melted, the composition is detected by a direct reading spectrometer. After reaching the predetermined furnace temperature, it is poured into a ladle and then cast at a set pouring temperature of 1580°C. In order to prevent the ceramic preform from shifting or floating during the subsequent casting process, an iron nail is inserted at the bottom of the ceramic preform when preparing it, so that it is fixed in the cavity and will not shift or float.
[0050] (8) After casting, the mixture was naturally cooled and demolded to obtain a ceramic reinforced high chromium iron-based composite material. The composite material is shown in FIG. Figure 2 The composite material of this embodiment is denoted as SiC@Ni / HCCI.
[0051] Example 2
[0052] This embodiment provides a ceramic reinforced high chromium iron-based composite material, and the preparation method thereof is as follows:
[0053] (1) Decontamination: Take an appropriate amount of ZTA (zirconia toughened alumina) ceramic particles, soak them in anhydrous ethanol at room temperature, and clean them in an ultrasonic cleaner for 5 minutes. The ZTA ceramic particles are 2 mm in size. The dust and impurities on the surface of the particles are washed away by cleaning. The SEM of ZTA ceramic particles is as follows: Figure 1 as shown in (b).
[0054] (2) Roughening: After decontamination, the ceramic particles are washed three times with deionized water to remove as much residual anhydrous ethanol as possible and then dried. The silicon carbide particles are then immersed in the roughening solution for 10 minutes, and the reaction container must be shaken continuously during the soaking. The roughening solution is prepared from 10 mL of hydrofluoric acid (mass concentration 44%) and an appropriate amount of deionized water to make 200 mL of roughening solution, and the ratio of hydrofluoric acid to deionized water is 1:19.
[0055] (3) Sensitization: Wash the ceramic particles after the roughening step three times with deionized water to remove the residual hydrofluoric acid, then put the ceramic particles into the prepared sensitizing solution and soak for 30 minutes. The reaction container must be shaken continuously during soaking. The main component of the sensitizing solution is 16.5g / L SnCl2·2H2O. When preparing the sensitizing solution, weigh a certain mass of SnCl2·2H2O and add it to an appropriate amount of deionized water. The solution will appear milky white. Then add an appropriate amount of hydrochloric acid to make the stannous chloride solution clear, and then add deionized water until the sensitizing solution reaches a fixed volume.
[0056] (4) Activation: Place the ceramic particles in the activation solution and soak for 20 minutes. The reaction container must be shaken continuously during the soaking process. The main component of the activation solution is 0.28g / L PdCl2. When preparing the activation solution, first weigh an appropriate amount of PdCl2 particles and add them to deionized water to dissolve them in deionized water. Take 2mL of hydrochloric acid and add it. The solution will turn brown and continue to stir until the PdCl2 is completely dissolved. During the activation process, the reaction container must be shaken several times to make the Pd 2+ As much as possible is reduced to metallic Pd, covering a large number of Pd catalytic nuclei on the surface of the ceramic particles.
[0057] (5) Chemical plating: A chemical plating layer is plated on the surface of the ceramic particles after decontamination, roughening, sensitization and activation by chemical plating. The chemical plating solution formula is 25g / L NiSO4, 15g / L C6H8O7, 10mL / LC3H6O3, 10mL / L (NH4)2MoO4, 30g / LNaH2PO2, 25g / L CH3COONa, and during the chemical plating process, the chemical plating solution is heated in a water bath to a temperature of 80°C, the pH is maintained between 5.0-5.2, and the plating time is 60min.
[0058] (6) Preparation of ceramic preform: Ceramic powder is used to coat the surface of ceramic particles to form a ceramic preform. Water glass is used as a binder and ceramic powder is used as a casting infiltrant. The binder and the casting infiltrant are dissolved in a ratio of 1.9:1 to prepare a coating material. The prepared coating material and ceramic particles are then put into a blender in a mass ratio of 7.2:100 and stirred evenly so that the coating material fully coats the ceramic particles. Ceramic powder is composed of silicon dioxide, aluminum oxide, copper oxide, boron carbide and titanium dioxide mixed in a ratio of 1:1.5:1:2:1.
[0059] The uniformly stirred ceramic particles and coating material are poured into a foam mold and dried to form a cylindrical preform with a diameter of 20 mm and a height of 10 mm. After the preform is solidified, it is fixed in the mold cavity and waits for pouring. In the process of preparing the ceramic preform, an iron nail is inserted into the bottom of the preform so that it can be fixed in the mold cavity later, and the prepared ceramic preform is naturally hardened.
[0060] (7) Preparation of composite materials: The prepared ceramic preform is assembled with the foam pattern and the casting system, the shape is trimmed and the slurry is applied, and the preform is placed in a sand box for casting.
[0061] During the casting process, an electric arc furnace is used to melt high chromium iron. After the high chromium iron is melted, its composition is detected by a direct reading spectrometer. After reaching the predetermined furnace temperature, it is poured into a ladle and then cast at a set pouring temperature of 1580°C.
[0062] (8) After casting, the mixture was naturally cooled and demolded to obtain a ceramic reinforced high chromium iron matrix composite material. Figure 2 The composite material of this embodiment is denoted as ZTA@Ni / HCCI.
[0063] Comparative Example 1
[0064] This comparative example is based on Example 1, and does not include steps (2) to (5) in Example 1. The remaining steps and conditions are the same as those in Example 1. In this example, the ceramic particles are not subjected to metallization modification treatments such as "roughening, sensitization, activation, and chemical plating". The composite material finally prepared is recorded as SiC / HCCI.
[0065] Comparative Example 2
[0066] This comparative example is based on Example 2 and does not include steps (2)-(5) in Example 1. The remaining steps and conditions are the same as those in Example 2. In this example, the ceramic particles are not subjected to metallization modification treatments such as "roughening, sensitization, activation, and chemical plating". The composite material finally prepared is recorded as ZTA / HCCI.
[0067] The composition, hardness and friction coefficient of the four composite materials prepared in Examples 1-2 and Comparative Examples 1-2 were analyzed. The analysis results are as follows: Figure 3-5 shown.
[0068] like Figure 3 As shown, they are SiC / HCCI (such as Figure 3 a), SiC@Ni / HCCI (such as Figure 3 b), ZTA / HCCI (such as Figure 3 c) and ZTA@Ni / HCCI (such as Figure 3 d) Microscopic morphology of the cross-section of the four composite materials. The ceramic particles are distributed in the HCCI matrix. The interface between the ceramic particles and the high chromium cast iron is tightly bonded, and no casting defects such as holes and gaps are observed.
[0069] The microhardness of four composite materials and metal matrix HCCI was analyzed, and the results are as follows: Figure 4. It can be seen from the figure that, compared with the HCCI metal substrate, the hardness improvement effect of the unmetallized ceramic particle reinforced composite materials SiC / HCCI and ZTA / HCCI is not obvious, while the hardness of the ceramic reinforced composite materials SiC@Ni / HCCI and ZTA@Ni / HCCI after metallization modification is significantly increased. This shows that the embodiment of the present invention improves the interface bonding strength between the ceramic particles and the metal matrix by plating the Ni-P alloy coating on the surface of ceramic particles such as SiC or ZTA. The ceramic particles can effectively withstand the load transmitted by the metal matrix. The high-density dislocations formed by the interface phase produce a second phase strengthening effect, which inhibits the plastic deformation of the matrix, thereby showing a higher hardness. Among them, the hardness of the unmetallized ceramic particle reinforced composite materials SiC / HCCI and ZTA / HCCI were 474 (HV) and 468 (HV), respectively, and the hardness of the ceramic particle reinforced composite materials SiC@Ni / HCCI and ZTA@Ni / HCCI with Ni-P alloy coating on the surface reached 610 (HV) and 589 (HV), and the hardness values increased by 28.7% and 25.9%, respectively.
[0070] Furthermore, the friction and wear performance of the four composite materials and the metal matrix HCCI were analyzed, and the analysis results are shown in Table 1. It can be seen from the table that compared with the weight loss of the metal matrix HCCI, the weight loss of the four composite materials is smaller, but there are also large differences between the weight loss of the four composite materials. For example, due to the generation of Fe3Si brittle phase at the interface of SiC / HCCI composite material, when subjected to external load, brittle fracture or SiC particles fall off, resulting in a large weight loss; while the FeAl2O4 phase or NiFe2O4 and NiAl2O4 phase generated at the interface of ZTA / HCCI composite material and ZTA@Ni / HCCI composite material is a spinel-like phase, which can play a certain bearing capacity when subjected to external force, reducing wear and weight loss; Ni3Si interface phase is generated at the interface of SiC@Ni / HCCI composite material, and the composite material shows good wear resistance, indicating that the interface phase can significantly improve the interface bonding strength of the composite material and play a good bearing capacity.
[0071] Table 1:
[0072]
[0073] like Figure 5As shown in the figure, in the friction coefficient test of 0-30min, compared with the base material HCCI, the friction coefficients of SiC / HCCI composites and ZTA / HCCI composites are always larger, while those of ZTA@Ni / HCCI composites and SiC@Ni / HCCI composites are always smaller. Among them, the interface phase of SiC@Ni / HCCI composite can bear and transfer load well, with the smallest friction coefficient, the smallest wear amount, and the best wear resistance.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for modifying ceramic particles, characterized in that: The steps include: S1. Decontamination: cleaning and decontaminating SiC particles and / or ZTA particles; S2. Roughening: Use a roughening liquid to roughen the surface of the ceramic particles, the roughening liquid is a hydrofluoric acid solution with a mass concentration of 2-2.5%; S3, sensitization: remove the roughening solution remaining on the surface of the ceramic particles, and transfer the ceramic particles into the sensitizing solution, which is an acidified solution containing 0.06-0.08 mol / L divalent tin; S4, activation: transferring the ceramic particles into an activation solution, wherein the activation solution is an acidified solution containing 0.0012-0.0024 mol / L divalent palladium; S5. Chemical plating: The ceramic particles are chemically plated using a chemical plating solution, wherein the chemical plating solution contains: 20-30 g / L NiSO4, 12-18 g / L C6H8O7, 8-12 mL / L C3H6O3, 8-12 mL / L (NH4)2MoO4, 25-35 g / L NaH2PO2 and 20-30 g / L CH3COONa; the pH of the chemical plating solution is 5.0-5.2; S6. Coating: Ceramic particles are coated with ceramic powders. The coating method is as follows: water glass is used as an adhesive, ceramic powders and the adhesive are mixed in a mass ratio of 1:1.8-2.2 to form a coating material, and the ceramic particles are coated with the coating material.
2. The modification method according to claim 1, characterized in that: In S1, the ceramic particles are placed in ethanol at room temperature and ultrasonically cleaned for 3-10 minutes.
3. The modification method according to claim 1, characterized in that: In S2: first use deionized water to clean the ethanol remaining on the surface of the ceramic particles and then dry them. Then transfer the ceramic particles into the roughening solution and soak them for 8-15 minutes. During the soaking process, the container is constantly stirred or shaken.
4. The modification method according to claim 1, characterized in that: In S3: first use deionized water to wash the residue on the surface of the ceramic particles to obtain a roughening solution, and then transfer it to the sensitizing solution and soak it for 25-35 minutes. During the soaking process, the container is constantly stirred or shaken; when preparing the sensitizing solution, weigh an appropriate amount of SnCl2·2H2O solid and add it to deionized water. The solution appears milky white, and then add an appropriate amount of hydrochloric acid to make the solution clear, and then add deionized water until the sensitizing solution reaches a predetermined concentration.
5. The modification method according to claim 1, characterized in that: In S4: the ceramic particles are placed in the activation solution and soaked for 16-24 minutes, and the container is continuously stirred or shaken during the soaking process. The activation solution is prepared by weighing PdCl2, adding it to deionized water, and then adding an appropriate amount of hydrochloric acid to completely dissolve the PdCl2 and present a brown-yellow color.
6. The modification method according to claim 1, characterized in that: In S5: the chemical plating solution formula is: 25g / L NiSO4, 15g / L C6H8O7, 10mL / L C3H6O3, 10mL / L (NH4)2MoO4, 30g / L NaH2PO2 and 25g / L CH3COONa; the pH of the chemical plating solution is 5.0-5.
2.
7. The modification method according to claim 1, characterized in that: In S5: during the chemical plating process, the chemical plating solution is heated in a water bath, the chemical plating temperature is maintained at 75-82° C., and the chemical plating time is 40-90 min.
8. The modification method according to claim 1, characterized in that: In S6: in the coating material, the ceramic powder is composed of a mixture of silicon dioxide, aluminum oxide, copper oxide, boron carbide and titanium dioxide; during the coating process, the coating material and the ceramic particles are mixed at a ratio of 6.5-7.5:100, put into a mixer and stirred to mix well, so that the coating material is coated on the surface of the ceramic particles.
9. A method for preparing a ceramic reinforced high chromium iron-based composite material, characterized in that: include: Step 1: pouring the ceramic particles modified by the modification method according to any one of claims 1 to 8 into a mold and drying them to obtain a ceramic preform; Step 2: Assemble the ceramic preform and the mold cavity, cast the smelted high-chromium cast iron metal liquid at the casting temperature, cool it, and demold it; the high-chromium cast iron metal liquid penetrates into the ceramic preform to form a composite body with the ceramic preform.
10. A ceramic reinforced high chromium iron-based composite material, characterized in that: Prepared by the preparation method described in claim 9.
Citation Information
Cited By
High-performance metal ceramic composite grinding roller and preparation method thereof
CN121380712A
Production method and production device of ceramic composite iron-based wear-resistant casting
CN122076925A
A cemented carbide reinforced silicon-manganese bainite steel and a method for producing the same
CN122959611A